Tourism Attraction and Destination Image in Building Interest in Visiting Tourists : A Case Study of Red Lentera Beach - Adelia Pratama; Anggi Josetio Prayoga (Journal of Managiere and Business, 2024)
This research aims to find out how tourists' willingness to visit Lentera Merah Beach is influenced by the image of the destination and its tourist attractions. Questionnaires were distributed to visitors to Lentera Merah Beach as part of the research methodology. The results of the investigation show that the natural beauty, facilities and uniqueness of a destination's beaches are one of the factors that make the destination attractive to visitors and significantly influence their willingness to come. In addition, positive opinions about a location, such as its reputation, perceived safety, and high-caliber service, also influence tourists' desire to visit Lentera Merah Beach. The conclusions of this research have implications for destination managers, who must continue to improve tourist attractions and increase positive opinions of their places to attract more visitors.